Multi-layer System Architecture Model for the European Super Smart Grid - Makkonen, Mimosa (My University, 2026)
Europe is aiming to become the first climate neutral continent by 2050. This ambitious aim is affecting and challenging several industries. Energy sector is one of the largest greenhouse gas emitters and the energy revolution is in action. The amount of renewably produced en-ergy and electricity has increased enormously during recent decades. However, the state of the power networks all around Europe are in danger to form to be the bottleneck of the fu-ture development. The grid is in desperate need for attention and investments, to get to the next level of the modern renewable power production. The European Union and the Com-mission have published several incentives, rules and regulations which are legally binding or encouraging the Member States to evolve their power infrastructures. The grid is required to change to be more flexible, smart and interconnected. Cross-border connections and the utilisation of advanced metering and automation, together with distributed power genera-tion, are the most effective and efficient way to transform the grid operations to this century and beyond. The final goal is to create a European super smart grid, which combines the technological and ideological characteristics of the two seamlessly. Smart grid actions em-phasise local distributed generation and smart metering infrastructure with intelligent auto-mation, whereas super grid actions focus on wide-area connectivity and HVDC technology to transport power across the continent. Both therefore support the distributed energy genera-tion, decentralisation and flexibility. The super smart grid is relatively complex system, which can naturally be difficult to comprehend and manage. A new revised and extended architec-tural model and structurisation are required. The extended model created within this thesis research is based on an existing smart grid architecture model SGAM, but with the addition of super grid characteristics to serve the modern European power network fully. As the grid itself is required to be more flexible, the architecture model’s cube-like layered structure enables future development and advancements to be included and extended within.
Keywords: smart grids; renewable energy sources; energy technology; data communications networks; fi=Sähkö- ja energiatekniikka|en=Electrical Engineering and Energy Technology|; Master’s Programme in Smart Energy